Playful methologies to reinforce the engagement in the security person of a higher educational institution - Carrasco Tineo, Carlos Darwin (2021)
This research had the general objective of demonstrating that the application of recreational methodologies will reinforce engagement in the security personnel of a Higher Educational Institution in the Lambayeque Region. The nature of the research was of a single-case, pre-experimental quantitative type, with an application study design, we worked with a population sample made up of 21 security agents. For statistics, descriptive and inferential statistics were used from the adapted evaluation instrument, "Engagement´s Test", made up of 27 items and three dimensions: absorption, dedication and vigor, which is supported by Humanist Theory and the Positivist Theory. The instrument was validated, thanks to the experts' criteria, in addition to using the item-test correlation validity, with a discrimination index (0.36 to 0.61); Also, Aiken's V (0.94) and instrument reliability were applied with Cronbach's Alpha (0.86). Together, the diagnosis was obtained (pre-test): obtaining: Low Level with (38%); the Medium Level with (52%); and the High Level with (10%). and continuing with the design of the program, and once this was applied, the post-test was obtained, which helped to verify the eradication of the low level, and obtain: a Medium Level with (52%), and a High Level with ( 48%). It should be added that, for the choice between the alternate and null hypotheses, the Wilcoxon Test (0.007) was applied; choosing thus, the Hi. Reaching a level of significance of p_value = 0.001 <0.05, affirming that the playful methodologies allowed to reinforce engagement in said personnel.